Suppressor of IKKɛ is an essential negative regulator of pathological cardiac hypertrophy - Ke-Qiong Deng; Aibing Wang; Yan-Xiao Ji; Xiao-Jing Zhang; Jing Fang; Yan Zhang; Peng Zhang; Xi Jiang; Lu Gao; Xue-Yong Zhu; Yichao Zhao; Lingchen Gao; et al. (Nature Communications, 2016)
Abstract Although pathological cardiac hypertrophy represents a leading cause of morbidity and mortality worldwide, our understanding of the molecular mechanisms underlying this disease is still poor. Here, we demonstrate that suppressor of IKKɛ (SIKE), a negative regulator of the interferon pathway, attenuates pathological cardiac hypertrophy in rodents and non-human primates in a TANK-binding kinase 1 (TBK1)/AKT-dependent manner. Sike-deficient mice develop cardiac hypertrophy and heart failure, whereas Sike-overexpressing transgenic (Sike-TG) mice are protected from hypertrophic stimuli. Mechanistically, SIKE directly interacts with TBK1 to inhibit the TBK1-AKT signalling pathway, thereby achieving its anti-hypertrophic action. The suppression of cardiac remodelling by SIKE is further validated in rats and monkeys. Collectively, these findings identify SIKE as a negative regulator of cardiac remodelling in multiple animal species due to its inhibitory regulation of the TBK1/AKT axis, suggesting that SIKE may represent a therapeutic target for the treatment of cardiac hypertrophy and heart failure.